The Influence of Servant Leadership on The Character of Teachers at Catholic Junior High School Stella Maris Tomohon - Bernadina Waha Labuan; Stefhanus Hanny Pangemanan (Eduvest - Journal of Universal Studies, 2024)
Servant Leadership is a leadership concept oriented towards serving others. The practice of Servant Leadership is also carried out by teachers in schools, with each having their own unique characteristics. This research aims to understand the reality of Servant Leadership and teacher characteristics, as well as to analyze whether there is an influence of servant leadership on teacher characteristics at Catholic Junior High School Stella Maris Tomohon. This research is of the quantitative type, with the research variables being Servant Leadership (X) and Teacher Characteristics (Y). Data were collected using questionnaires. The analysis technique used was simple regression analysis. The results of hypothesis testing show that the Servant Leadership variable (X) has a significant positive influence on the Teacher Characteristics variable (Y). This is because the significance value 0.014 < probability 0.05 and the calculated T value is greater than the tabled T value 2.034 (3.138 < 2.034). For leaders at Catholic Junior High School Stella Maris Tomohon, it is important to consider input from others, especially teachers and staff. For teachers at Catholic Junior High School Stella Maris Tomohon, it is important to always pay attention to their characteristics as teachers, which include being humble, skilled at managing time, respecting the process, being open-minded, and being confident as important indicators in shaping teacher characteristics.